The Implementation of Differentiated Instruction Integrated with Technology in English Class at SMA Negeri 7 Denpasar - Komang Kurnia Octa Della Putri; Putu Adi Krisna Juniarta; Gede Mahendrayana (Jurnal Pendidikan dan Sastra Inggris, 2026)
This study investigated the implementation of differentiated instruction integrated with technology in English classrooms and students’ interest in its implementation at SMA Negeri 7 Denpasar. An exploratory sequential mixed-methods design was applied. The qualitative phase involved classroom observations focusing on content, process, and product differentiation supported by technology. The quantitative phase used a 20-item Likert-scale questionnaire to measure students’ interest based on enjoyment, attraction, attention, and involvement. The participants were one English teacher and 106 tenth-grade students from three classes (X8, X9, and X10), selected through purposive sampling. Qualitative data were analyzed using an interactive model, while quantitative data were analyzed using descriptive statistics. The findings showed that the teacher implemented differentiated instruction through varied learning materials, ability-based grouping, and flexible product options supported by digital platforms. The results revealed that students’ interest was categorized as high, with a mean score of 72.5. Students demonstrated positive engagement reflected in their enjoyment, attraction, attention, and involvement. Overall, the findings indicate that differentiated instruction integrated with technology supports both instructional practices and students’ interest in learning English.